2020
DOI: 10.5603/imh.2020.0032
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among 3712 Greek seafarers

Abstract: Background: Global concern on seafarers' health and its potential cost is widely evident across the shipping industry. Seafarers are at increased cardiovascular risk since it is common to have risk factors associated with that risk such as hyperlipidaemia, obesity and smoking. The aim of this study is to assess the prevalence of the main risk factors for cardiovascular disease (CVD), i.e. hyperlipidaemia, smoking and obesity, in Greek seafarers. Materials and methods: During pre-embarkation medical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A high intake of sodium is associated with an increased risk of various chronic diseases, such as hypertension, stroke, and cardiovascular disease. A recent study reported that seafarers are at an increased risk of cardiovascular disease due to common unhealthy eating patterns, smoking, hyperlipidemia, and obesity [ 28 ]. Considering our results, students undertaking shipboard internships need to focus on healthy eating management to prevent chronic diseases and become healthy seafarers.…”
Section: Discussionmentioning
confidence: 99%
“…A high intake of sodium is associated with an increased risk of various chronic diseases, such as hypertension, stroke, and cardiovascular disease. A recent study reported that seafarers are at an increased risk of cardiovascular disease due to common unhealthy eating patterns, smoking, hyperlipidemia, and obesity [ 28 ]. Considering our results, students undertaking shipboard internships need to focus on healthy eating management to prevent chronic diseases and become healthy seafarers.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of risk class C among older seafarers indicates the need for increased medical surveillance and interventions targeting age-related health conditions. As seafarers advance in age, they may experience a higher burden of chronic diseases that can affect their fitness for work [1,15,16]. Implementing more frequent health screenings and preventive measures specific to age-related conditions can help mitigate the impact of these health is- sues and ensure the continued well-being of older seafarers [17].…”
Section: Discussionmentioning
confidence: 99%